Fullerenes and Other Carbon-Rich Nanostructures - Nierengarten, Jean-François.; Nierengarten, Jean-François. (Structure and Bonding,, 2014)
Yanfei Shen Takashi Nakanishi Exotic Self-Organized Fullerene Materials Based on Uncommon Hydrophobic–Amphiphilic Approach Yuming Zhao Guang Chen C60 Fullerene Amphiphiles as Supramolecular Building Blocks for Organized and Well-Defined Nanoscale Objects Anna Troeger Vito Sgobba Dirk M. Guldi Multilayer Assembly for Solar Energy Conversion Delphine Felder-Flesch Self- or Induced Organization of [60]Fullerene Hexakisadducts   Andrés de la Escosura Olga Trukhina Tomás Torres Dual Role of Phthalocyanines in Carbon Nanostructure-Based Organic Photovoltaics   Riccardo Marega Davide Giust Davide Bonifazi Supramolecular Chemistry of Carbon Nanotubes at Interfaces: Toward Applications   Stephanie Frankenberger Johanna A. Januszewski Rik R. Tykwinski Oligomers from sp-Hybridized Carbon: Cumulenes and Polyynes.